Out-patient flexible carbon dioxide laser surgery for benign laryngopharyngeal pathologies via transnasal flexible laryngo-oesophagoscopy. Issue 7 (20th April 2017) - Mohammed, H; Masterson, L; Nassif, R
Abstract: Objective: To assess the feasibility and outcomes of flexible carbon dioxide laser surgery in a clinic-based setting. Methods: A prospective study was conducted in a tertiary centre. Clinical indications, clinical outcomes and patient satisfaction were assessed in patients treated with flexible carbon dioxide laser surgery via transnasal endoscopy and followed up over a period of up to nine months. Patients who were not fit for general anaesthesia or those with lesions that cannot be accessed by micro-laryngoscopy were included. Results: A total of 13 patients (14 procedures) were included. Clinical indications for surgery were small-to-medium sized benign pathologies in the upper aero-digestive tract. Patient satisfaction was assessed using a validated questionnaire. Conclusion: Early data suggest that flexible carbon dioxide laser is a versatile and feasible instrument with potential applications for a range of benign pathologies in the upper aero-digestive tract.